2023
DOI: 10.1002/nur.22327
|View full text |Cite
|
Sign up to set email alerts
|

Psychological safety, communication openness, nurse job outcomes, and patient safety in hospital nurses

Abstract: Promoting psychological safety in a workplace is known to contribute to improved job outcomes across a wide variety of industries. This study aimed to examine the relationships between psychological safety at work and job outcomes (i.e., job satisfaction and intention to leave), and patient safety among hospital nurses; and to determine the mediating effect of communication openness on these relationships.This cross-sectional study used survey data from 867 hospital nurses working in the United States. Multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 49 publications
(97 reference statements)
0
0
0
Order By: Relevance
“…, 2004). Based on a report of a research done at Google, it was found that members value those teams which are high on PS (Cho et al. , 2023).…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…, 2004). Based on a report of a research done at Google, it was found that members value those teams which are high on PS (Cho et al. , 2023).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Moreover, in a high-quality relationship with leaders, employees experience high psychological safety (PS) for generating, promoting and implementing novel ideas and exhibiting positive behaviors (Carmeli et al. , 2010; Cho et al. , 2023).…”
Section: Introductionmentioning
confidence: 99%